Bivalvos del Pliensbachiense en la Sección de Almonacid de la Cuba (Cordillera Ibérica, España) - Comas-rengifo, María José; Valls, Jorge; Goy, Antonio (Coloquios de Paleontología, 2004)
A collection of one hundred ninety specimens Pliensbachian Bivalves from the Almonacid de la Cuba region (Zaragoza) has been analysed. As a result, twenty species included in fourteen genera are described. These species are included into the Subclass Pteriomorphia (14%; Mytiloidea, Pinnoidea, Limoidea, Ostreoidea y Pectinoidea) and mostly in the Subclass Heteroconchia (86%; Lucinoidea, Cardioidea y Pholadomyoidea). Preservation in the Pteriomorphia suggests that, at least one of the wall layer was originally calcitic, whereas in the Heteroconchia (only recorded as internal moulds), the wall composition was entirely aragonitic. The 61% of the studied specimens are included in the Superfamily Pholadomyoidea, which is also the Superfamily with a higher taxonomic diversity. The lifestyle of these Pliensbachian bivalves suggests that the energy in the environment decreased between the Río Palomar and Almonacid de la Cuba Formations. Nevertheless, in the upper pat of the latter, a period of high energy is recognised. The bivalves from Cerro del Pez Formation suggest that the energy in this formation was even lower than in the Almonacid de la Cuba Formation. The increase in the byssate epifaunal and cemented bivalves in the Barahona Formation suggests the highest energy environment of the all studied formations.
Keywords: Systematic; Bivalvia; Pliensbachian; Lower Jurassic; Iberian Range; Spain